1998
DOI: 10.1046/j.1365-2672.1998.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of conjugated linoleic acid by dairy starter cultures

Abstract: J. JIANG, L. BJÖ RCK AND R. FONDÉ N. 1998. Nineteen different strains of lactobacilli, lactococci, streptococci and propionibacteria commonly used as dairy starter cultures were tested for their ability to produce conjugated linoleic acid (CLA) from free linoleic acid in vitro. Two strains of Propionibacterium freudenreichii ssp. freudenreichii and one strain of P. freudenreichii ssp. sheramnii were found to be capable of converting free linoleic acid to extracellular CLA. The highest level of CLA formed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
218
1
12

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 22 publications
17
218
1
12
Order By: Relevance
“…As in the present work, Gnädig et al [32] and Jiang et al [42] found no effect of the manufacturing conditions on the CLA content of a French Emmental cheese and of two common types of Swedish hard cheeses, respectively. In contrast, in some cases weak positive or negative variations have been observed during the manufacture of Cheddar cheese [48] or processed cheese [29], which could be explained either by free-radical-type oxidation of linoleic acid, likely during aging and heat treatment [34], or by conversion of free linoleic acid into CLA by the dairy starter cultures [43,48]. However, although the ripening time, heating level and microflora composition varied between the different cheeses studied in the present work, the effect of these manufacturing parameters on the CLA content of cheese fat was negligible in comparison with that of the original milk composition.…”
Section: Fatty Acidsmentioning
confidence: 89%
“…As in the present work, Gnädig et al [32] and Jiang et al [42] found no effect of the manufacturing conditions on the CLA content of a French Emmental cheese and of two common types of Swedish hard cheeses, respectively. In contrast, in some cases weak positive or negative variations have been observed during the manufacture of Cheddar cheese [48] or processed cheese [29], which could be explained either by free-radical-type oxidation of linoleic acid, likely during aging and heat treatment [34], or by conversion of free linoleic acid into CLA by the dairy starter cultures [43,48]. However, although the ripening time, heating level and microflora composition varied between the different cheeses studied in the present work, the effect of these manufacturing parameters on the CLA content of cheese fat was negligible in comparison with that of the original milk composition.…”
Section: Fatty Acidsmentioning
confidence: 89%
“…However, in the present organism such a reductive reaction sequence did not occur since the formed cis-9, trans-11 isomer of CLA was not converted further to other fatty acids. Instead, detoxification of LA via conversion to CLA as proposed by Jiang et al [5] is a more probable physiological role for the isomerization in the present organism. Jiang et al [5] observed a positive correlation between CLA formation and the ability to tolerate LA among three CLAforming strains of propionibacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases a major proportion of CLA formed has been in the cis-9, trans-11 configuration. The conversion reaction has been studied both in bacterial growing cultures and washed-cell suspensions [5,9,12,13,17,20]. From these small-scale microbiological isomerization studies one can conclude that the toxicity of LA and its low solubility in aqueous solutions may have severe complications in the production of CLA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings that certain strains of propionibacteria [30,65,71,77 and others] or their enzyme extract [46] can transfer linoleic acid effectively into CLA with high conversion rates of up to 87%, further investigations were carried out. Xu et al [83] investigated 11 probiotic bacteria for the ability to form CLA.…”
Section: Propionibacteriamentioning
confidence: 99%
“…Jiang et al [30] screened 19 different strains of lactobacilli, lactococci, streptococci and propionibacteria commonly used as dairy starter cultures for their ability to produce conjugated linoleic acid (CLA) from free linoleic acid in vitro. Two strains of Propionibacterium freudenreichii ssp.…”
Section: Influence Of Dairy Starter Culturesmentioning
confidence: 99%